Chiropractic management of postoperative spine pain: a report of 3 cases - Coulis, Christopher M. (Elsevier, 2013)
OBJECTIVE: The purpose of this case series is to describe chiropractic care including spinal manipulation for 3 patients with postsurgical spine pain. CLINICAL FEATURES: Three patients with postsurgical spine pain (1 cervical fusion, 1 lumbar discectomy, and 1 lumbar laminectomy) presented for chiropractic treatment at a major US medical center. Treatment included spinal manipulation and/or flexion-distraction mobilization based on patient response to joint loading strategies. INTERVENTION AND OUTCOMES: Two patients were treated with high-velocity, low-amplitude spinal manipulation; and 1 patient was treated with flexion-distraction mobilization. Treatment frequency and duration were 4 treatments over 4 weeks for case 1, 17 treatments over 7 years for case 2, and 5 treatments over 5 weeks for case 3. Subjective improvement was noted using numeric pain scores and functional changes; and upon completion, the patients reported being “satisfied” with their overall outcome. One episode of transient benign soreness was noted by 1 patient. No additional adverse events or effects were noted. CONCLUSION: In these 3 cases, patients with postsurgical spine pain responded positively to chiropractic care. Spinal manipulation/mobilization was tolerated without significant adverse effects.